2019
DOI: 10.1007/s00421-019-04275-7
|View full text |Cite
|
Sign up to set email alerts
|

Criterion validity of the Ekblom-Bak and the Åstrand submaximal test in an elderly population

Abstract: The aim of this study was to validate the submaximal Ekblom-Bak test (EB-test) and the Åstrand test (Å-test) for an elderly population. Methods Participants (n = 104), aged 65-75 years, completed a submaximal aerobic test on a cycle ergometer followed by an individually adjusted indirect calorimetry VO 2 max test on a treadmill. The HR from the submaximal test was used to estimate VO 2 max using both the EB-test and Å-test equations. Results The correlation between measured and estimated VO 2 max using the EB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…However, similar to our findings that self-reported physical activity was associated with difference between measured and estimated VO 2 max L min −1 levels, prior studies ( Bjorkman et al, 2016 ; Vaisanen et al, 2020 ) have found that individuals with lower CRF levels are more likely to have overestimated VO 2 max values with the EB method. One possible explanation for overestimation of VO 2 max values with the EB method in this study is that for safety and participant convenience reasons, the submaximal test was always performed before the maximal exercise test on the same day.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, similar to our findings that self-reported physical activity was associated with difference between measured and estimated VO 2 max L min −1 levels, prior studies ( Bjorkman et al, 2016 ; Vaisanen et al, 2020 ) have found that individuals with lower CRF levels are more likely to have overestimated VO 2 max values with the EB method. One possible explanation for overestimation of VO 2 max values with the EB method in this study is that for safety and participant convenience reasons, the submaximal test was always performed before the maximal exercise test on the same day.…”
Section: Discussionsupporting
confidence: 89%
“…A recently developed Ekblom-Bak (EB) cycle ergometer test (Ekblom-Bak et al, 2014;Bjorkman et al, 2016) for prediction of VO 2 max is low-risk, easy to administer, and shown to be valid for a wide range of aerobic capacities and ages (Vaisanen et al, 2020). The initially reported (Ekblom-Bak et al, 2014) association between estimated and observed VO 2 max using the EB method was r = 0.91, and showed significant improvements on corresponding coefficient of variation (9.3%) compared to the Åstrand-Rhyming method (18.0%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prediction formula established by Björkman et al 18 using the Åstrand submaximal cycling test can explain 50% of the variation in , with an SEE of 5.6 mL kg −1 min −1 . The validity correlation coefficient of predicted by Väisänen et al 21 , Ekblom‐Bak et al 23 , and Swain et al 46 using the Åstrand submaximal cycling test was 0.49–0.83, with SEEs of 5.8 mL kg −1 min −1 , 0.5 L min −1 , and 5.4 mL kg −1 min −1 , respectively. Beekley et al 22 found a moderate relation (r = 0.63, p < 0.05) between the predicted through the YMCA submaximal cycling test and the measured , with an SEE of 9.8 mL kg −1 min −1 .…”
Section: Discussionmentioning
confidence: 75%
“…These advantages have promoted the development of submaximal cycling tests, including the Astrand-Ryhming, Young Men’s Christian Association (YMCA) and Ekblom-Bak tests 17 – 20 . However, it has been observed that prediction models established through these submaximal cycle ergometer tests tend to overestimate in healthy men with low fitness levels and underestimate it in those with high fitness levels 21 , 22 . Consequently, there is a pressing need to develop a new formula that can provide a more precise and individualized estimation of in healthy men.…”
Section: Introductionmentioning
confidence: 99%